2003
DOI: 10.1103/physrevc.68.044609
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate energy Coulomb excitation as a probe of nuclear structure at radioactive beam facilities

Abstract: The effects of retardation in the Coulomb excitation of radioactive nuclei in intermediate energy collisions (E lab ∼ 100 MeV/nucleon) are investigated. We show that the excitation cross sections of low-lying states in 11 Be, 38,40,42 S and 44,46 Ar projectiles incident on gold and lead targets are modified by as much as 20% due to these effects. The angular distributions of decaying gammarays are also appreciably modified. 25.70.De

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(76 citation statements)
references
References 31 publications
3
73
0
Order By: Relevance
“…[27] has shown that at 10 MeV/nucleon the relativistic corrections are important only at the level of 1%. At 500 MeV/nucleon, the correct treatment of the recoil corrections is relevant on the level of 1%.…”
Section: Intermediate Energy Coulomb Excitationmentioning
confidence: 99%
See 1 more Smart Citation
“…[27] has shown that at 10 MeV/nucleon the relativistic corrections are important only at the level of 1%. At 500 MeV/nucleon, the correct treatment of the recoil corrections is relevant on the level of 1%.…”
Section: Intermediate Energy Coulomb Excitationmentioning
confidence: 99%
“…from Coulomb excitation experiments at intermediate energies requires a proper treatment of special relativity [27,31]. The dynamical relativistic effects have often been neglected in the analysis of experiments elsewhere (see, e.g.…”
Section: Intermediate Energy Coulomb Excitationmentioning
confidence: 99%
“…[49] has shown that at 10 MeV/nucleon the relativistic corrections are important only at the level of 1%. At 500 MeV/nucleon, the correct treatment of the recoil corrections is relevant on the level of 1%.…”
Section: Pos(enas 6)023mentioning
confidence: 99%
“…from Coulomb excitation experiments at intermediate energies requires a proper treatment of special relativity [49,50]. The dynamical relativistic effects have often been neglected in the analysis of experiments elsewhere (see, e.g.…”
Section: Pos(enas 6)023mentioning
confidence: 99%
“…There has been some effort devoted to estimate the consequences of this lack of inertiality in the reference system [19,20]. We would like here to do it in our own way, as we think that the working frame developed in Sec.…”
Section: Study Of the Recoilmentioning
confidence: 99%